2020
DOI: 10.21475/ajcs.20.14.01.p1960
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Avena spp. to different concentration levels of Meloidogyne javanica and M. incognita inoculum

Abstract: The objective of this study was to evaluate the resistance reaction of Avena spp. after inoculation of different concentrations of eggs and juveniles of M. javanica and M. incognita. Ten oat genotypes (Avena sativa: UPFPS Farroupilha, UPFA Ouro, IPR Afrodite, AF1345 Ucraniana; A. strigosa: Agro Quaraí, Agro Esteio, Embrapa 139, Iapar 61 Ibiporã, UPFA 21 Moreninha, AF 12202) were evaluated in bioassays for resistance against the root-knot nematodes, Meloidogyne javanica and M. incognita. Susceptible (Solanum l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The results agree with those of Machado et al (2015), who found that the RF of M. javanica and other Meloidogyne species on the cultivar was 0. Previous reports of the resistance of IPR Afrodite (Marini et al, 2016;Lemes et al, 2020) and its ability to reduce M. javanica and M. incognita penetration (Marini et al, 2016) can be found in the literature. IAPAR 61 Ibiporã was resistant to M. javanica, with an RF of 0.6 (Gabriel et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The results agree with those of Machado et al (2015), who found that the RF of M. javanica and other Meloidogyne species on the cultivar was 0. Previous reports of the resistance of IPR Afrodite (Marini et al, 2016;Lemes et al, 2020) and its ability to reduce M. javanica and M. incognita penetration (Marini et al, 2016) can be found in the literature. IAPAR 61 Ibiporã was resistant to M. javanica, with an RF of 0.6 (Gabriel et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the effect of the nematode species, we found that, for all variables evaluated, the effect obtained by M. incognita was more significant when compared to M. javanica. This effect is expected since it is known that M. incognita is more aggressive to the roots of host plants compared to M. javanica, which may lead to its higher ability to infect root tissue (Carraro-Lemes et al, 2020;Inomoto, 2016).…”
Section: Species Of Microorganism Used In Biocontrolmentioning
confidence: 99%